Spectral properties of indotricarbocyanine dye in tissues of experimental animals - M. P. Samtsov; D. S. Tarasov; A. Р. Lugovski; Р. Т. Petrov; A. О. Savin; R. D. Zilberman; E. S. Voropay (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The paper presents the results of studies of the spectral properties of a photosensitizer based on indotricarbocyanine dye when accumulating in tissues of experimental animals. Using laser fluorescence spectroscopy, the in vivo and ex vivo fluorescence spectra of tissue-localized indotricarbocyanine dye were obtained for different time counts after intravenous administration. The profile of the pharmacokinetics of its accumulation and withdrawal was determined from the change in the intensity of fluorescence in the tumor and healthy muscle tissues of the photosensitizer. A monotonic deformation of its fluorescence spectrum was revealed in the tissues of tumor nodes and muscles of the thigh when registered through the skin over time after intravenous administration. The achievement of the maximum accumulation of the photosensitizer in the tumor correlates with the stabilization of the shape of its in vivo fluorescence spectrum. Thus, the maximum shift can be used as a diagnostic indicator of the maximum accumulation of indotricarbocyanine photosensitizer in the tumor tissues. The results were confirmed for two groups of animals: the first one – black mice of the C57Bl/6 line with an inoculated tumor of Clone M3 melanoma, the second – white mice of the ICR line with an inoculated tumor of Ehrlich ascites carcinoma. The analysis of the shape of the fluorescence spectrum of the photosensitizer during registration through the skin for animals with different colors has been carried out.